PENERAPAN MODEL PEMBELAJARAN TALKING STICK PADA MATA PELAJARAN AQIDAH AKHLAK DI MIN 22 HULU SUNGAI TENGAH - Mohammad Arief (CV. ADIBA ASIHA AMIRA, 2024)
The selection of the right learning model can support the achievement of learning objectives in the classroom. The subject of Aqidah Akhlak contains the basics of religion and Islamic moral values. Therefore, a learning model is needed that can help teachers and students in developing learning activities and creativity. One of the effective methods to be applied to learning Aqidah Akhlak is the Talking Stick learning model. Because this learning model can create student activity in acquiring intellectual skills, attitudes, and motor skills. In addition, it can generate positive responses, can create better relationships between friends, and can instill an attitude of self-confidence and responsibility. Learning Aqidah Akhlak with the Talking Stick learning model provides students with the opportunity to practice expressing opinions, speaking, and self- confidence so as to create a pleasant atmosphere. The Talking Stick learning model is implemented in learning Aqidah Akhlak at the MI level in grades III to VI.